1974
DOI: 10.1002/jso.2930060508
|View full text |Cite
|
Sign up to set email alerts
|

The management of malignant effusions from breast cancer

Abstract: We have reviewed our experience with 50 patients with malignant effusion secondary to breast cancer. Prior to any therapy for this problem the malignant cause of the effusion must be firmly established. Permanent cell block with cytologic examination of such cells proved exceedingly accurate in our hands. Once the diagnosis is known secondary to malignancy the type of effusion must be investigated since those in which there are a large number of free cells or diffuse serosal studding respond best to intracavit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0
1

Year Published

1977
1977
2019
2019

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 20 publications
(3 citation statements)
references
References 7 publications
0
2
0
1
Order By: Relevance
“…In all of the studies, except for the study reported by Rojato et al [14], the mean or median survival after the onset of pleural effusion ranges from 6 to 15 months, indicating a poor prognosis for this group of patients.…”
Section: Discussionmentioning
confidence: 97%
See 1 more Smart Citation
“…In all of the studies, except for the study reported by Rojato et al [14], the mean or median survival after the onset of pleural effusion ranges from 6 to 15 months, indicating a poor prognosis for this group of patients.…”
Section: Discussionmentioning
confidence: 97%
“…As shown in our study pleural effusion can occur as early as 1 month or as late as 19 years with a median interval of 27 months. Rojato et al [14], Raju et al [15], and Fentiman et al [16] have shown a median lag time of 24, 22 and 41.5 months respectively. When effusion occurs within 1 month of diagnosis of breast cancer, one is probably dealing with stage IV disease and clinical experience has proved that these patients have an generally poor prognosis.…”
Section: Discussionmentioning
confidence: 99%
“…Entre las diferentes modalidades terapéuticas para el derrame pleural, están la toracentesis, toracostomía con drenaje cerrado, pleurectomía, derivaciones pleuroperitoneales y la pleurodesis química, la cual es bastante utilizada, pero no es etiológica ni fisiológica 18,19 ; además, se han reportado en diferentes estudios los efectos de la absorción sistémica de algunos de los agentes empleados en dicho procedimiento, que pueden estar relacionados con síndrome de dificultad respiratoria aguda en algunas ocasiones 20,21 Los catéteres pleurales permanentes son una alternativa cada vez más usada para reemplazar la pleurodesis, permitiendo el drenaje domiciliario y manejo ambulatorio, aunque se asocia más con efectos adversos 22 .…”
unclassified